Conductive Nanostructured Scaffolds Render Low Local Current Density to Inhibit Lithium Dendrite Growth - Zhang, Rui; Cheng, Xin-Bing; Zhao, Chen-Zi; Peng, Hong-Jie; Shi, Jia-Le; Huang, Jia-Qi; Wang, Jinfu; Wei, Fei; Zhang, Qiang (Advanced materials (Weinheim), 2016)
A nanostructured lithium‐metal anode employing an unstacked graphene “drum” and dual‐salt electrolyte brings about a dendrite‐free lithium depositing morphology. On the one hand, the unstacked graphene framework with ultrahigh specific surface area guarantees an ultralow local current density that prevents the growth of lithium dendrites. On the other hand, the stable, flexible, and compact solid electrolyte interphase layer induced by the dual‐salt electrolyte protects the deposited lithium layers.